Ellis-van creveld syndrome: Report of two cases - Altaf Hussain Chalkoo; Mohsin Muzaffar Tak (Wolters Kluwer Medknow Publications, 2011)
Chondroectodermal dysplasia (Ellis-van Creveld syndrome) appears to involve all the embryonic layers. Nails, teeth and gums indicate the involvement of ectodermal layer; sometimes it may accompanied by eye and neural involvement. Abnormalities of the bones, heart, kidneys indicate the involvement of mesodermal involvement. Endodermal involvement though not very common but some patents may have lung and liver abnormalities. Oral signs are very peculiar and provide vital clue for the diagnosis and further counseling of such patients.